(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
Under N(oun)I(ncorporation), a N stem is compounded with a V stem to yield a complex V stem. After a survey of the most important approaches to the phenomenon, this paper describes some distinctions which have received little attention in the literature, mainly regarding the directionality and adjacency of the components. A new approach is introduced which distinguishes between incorporated XP Ns (preverbal) and X° Ns (postverbal): this approach is shown to clearly capture the alternations. KEYWORDS: noun incorporation, polysynthesis, morphology-syntax interface, native American languages, paleosiberian languages